The hyperglycemic and dyslipidemic effects of L-arginine in streptozotocin-induced diabetic rats (Journal of Fatima Jinnah Medical University, 2023)
Background: Diabetes is a serious disease which is posing a great risk to the overall health care all around the globe. Major factor in its systemic adverse effects is the enhancement of lipolysis by prolonged hyperglycaemia ultimately leading to dyslipidemia. This dyslipidemia is a big risk feature for all cardiovascular diseases related to most of the diabetic patients. L arginine blessed with antioxidant properties can play a substantial role in the prevention, and management of diabetes and related complications. The study was aimed at finding the novel uses of L-Arginine in diabetes.Subject and method: 15 adult Sprague Dawley rats , only female (to avoid pregnancy) weighing 250+ 50 g were used in this study which were divided equally (five rats each) into three groups randomly after ensuring that their lipid profiles and blood sugar were normal. After keeping one group as Normal Control Group (NC), the remaining two groups were made quasi-analogue Type II diabetic model through administration of Streptozotocin (35 mg/kg) in a single dose intra-peritoneal (IP). After lapse of 48 hours, all the rats of two groups had shown blood sugar levels over 300 mg/dl and therefore were taken as diabetic. One of the two diabetic groups was taken as “Positive Control” with DM rats (DM), while the other was taken as treatment group DM+L-ARG Group”. Results: With regards to fasting blood sugar (BSF), total cholesterol (T-Chol), triglyceride (TG), low density lipoprotein (LDL) and high density lipoprotein (HDL), Group III (DM+L-ARG) showed significant improvement with the p-value of less than 0.001.Conclusion: After conducting this experimental animal work, we are able to conclude that in Streptozotocin induced diabetic model, the novel use of antioxidant L-Arginine with good safety profile and minimal adverse effects also has significant anti-hyperglycemic and anti-lipidemic activity.
Keywords: L-Arginine; Diabetes Mellitus; Dyslipidemia; Hyperglycemia; Streptozotocin